2018
DOI: 10.1155/2018/2929107
|View full text |Cite|
|
Sign up to set email alerts
|

A Hop Extract Lifenol® Improves Postmenopausal Overweight, Osteoporosis, and Hot Flash in Ovariectomized Rats

Abstract: Objective In order to assess the effectiveness of a hop extract (HE) for postmenopausal symptoms, the effects of Lifenol on ovariectomy-induced osteoporosis, hyperlipidemia, body weight increase, and hot flash were investigated in rats. Methods Female Sprague-Dawley rats were ovariectomized and subjected to a daily scheduled exercise training (15 min at 15 m/min) or treated with HE (30 or 100 mg/kg, oral) or 17β-estradiol (100 μg/kg, intraperitoneal) for 12 weeks. Body and visceral fat weights, serum lipid pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 27 publications
3
8
0
Order By: Relevance
“…The histomorphometric analysis of the lumbar vertebrae showed that trabecular bone volume was significantly higher in XN-treated mice. The results confirming the beneficial effects of prenylated flavonoids on bone resorption associated with osteoporosis were also obtained by Ban et al [ 55 ]. The use of Lifenol ® , which contains hops extracts, in ovariectomized rats significantly reduced the decrease in bone mineral density and mineral content.…”
Section: Discussionsupporting
confidence: 87%
“…The histomorphometric analysis of the lumbar vertebrae showed that trabecular bone volume was significantly higher in XN-treated mice. The results confirming the beneficial effects of prenylated flavonoids on bone resorption associated with osteoporosis were also obtained by Ban et al [ 55 ]. The use of Lifenol ® , which contains hops extracts, in ovariectomized rats significantly reduced the decrease in bone mineral density and mineral content.…”
Section: Discussionsupporting
confidence: 87%
“…RHEC administration inhibited weight gain and abdominal fat accumulation, and this effect is similar to that seen after estrogen treatment in OVX rats [24]. is weight loss was not observed in the red clover alone [25]; weight loss was observed in high contents of xanthohumol in hops [26,27]. Biochanin A and xanthohumol contents in RHEC were approximately 1.09% and 0.033%, respectively.…”
Section: Discussionsupporting
confidence: 61%
“…In the RHEC group, an increase in TST was significantly suppressed under normal as well as under stress conditions. It was confirmed that TST decreased when 8-PN, one of the main components of hops, was administered to OVX rats [30]; moreover, it was found that changes in TST and rectal temperature decreased upon consumption of Lifenol ® [27], a standardized hops CO 2 extract. While the clinical test results of red clover for the iris have been abundantly reported [31], there are few Evidence-Based Complementary and Alternative Medicine reports about TST results in animals.…”
Section: Discussionmentioning
confidence: 79%
“…Treatments promoting the bone formation or inhibiting the bone resorption can achieve amelioration of PMOP, while estrogen deficiency may induce deterioration of PMOP. The ovariectomized rat model can simulate the pathological process of bone loss during the postmenopause stage in humans, and it has been widely used to evaluate the effects of drugs in PMOP [ 13 , 14 ]. We employed bilateral ovariectomy to establish the PMOP animal model, and the results are in accordance with these previous conclusions.…”
Section: Discussionmentioning
confidence: 99%